Delusions of Possession and Religious Coping in Schizophrenia: A Qualitative Study of Four Cases - Pietkiewicz, Igor J.; Kłosińska, Urszula; Tomalski, Radosław (Frontiers in Psychology, 2021)
The notion of evil spirits influencing human behaviour or mental processes is used in many cultures to justify various symptoms or experiences. It is also expressed in psychotic delusions of possession, but there is limited research in this area. This study explores how patients with schizophrenia came to the conclusion that they were possessed, and how this affected help-seeking. Interviews with two men and two women about their experiences and meaning-making were subjected to interpretative phenomenological analysis. Three main themes were identified: 1) Links between traumatic experiences and psychotic symptoms, 2) The emergence of religious themes in delusional contents, and 3) Reluctance to use medical treatment and instead to seek exorcism. In each case, attributing problems to possession was supported by the local environment and media, led to seeking spiritual help, and delayed diagnostic assessment and treatment. However, using religious coping contributed to the sense of predictability and social support. Clinicians are encouraged to explore the experiences and conflicts expressed by the symptoms which people ascribe to possession and to negotiate alternative explanatory models with their patients.